PERENCANAAN PELAKSANAAN PROYEK KONSTRUKSI KANTOR KPU KABUPATEN BADUNG - Pramesti, I Gusti Ayu Dina; Jawat, I Wayan; Eryani, I Gusti Agung Putu (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
Construction project implementation planning is an important stage that aims to optimize time, cost, and quality of work. In the construction project of the Badung Regency KPU Office Building, implementation planning is very crucial considering the location of the project which is in a densely populated area, so that an appropriate and efficient implementation method is needed. The problems faced are how to prepare an implementation schedule, calculate resource requirements, and plan costs systematically so that the project can run according to plan. This study uses the Precedence Diagram Method (PDM) to prepare the project schedule and Microsoft Project as a visualization tool. In addition, an analysis of human resource needs, materials, and tools was carried out as well as the preparation of the Implementation Cost Plan (RBP) and Budget Plan (RAB). The results of the study show that implementation planning using the PDM method produces a structured and efficient project schedule. The total cost obtained from the RBP analysis results is IDR 4,159,270,327.34, while the RAB reaches IDR 4,623,397,141.26, with a cost difference of IDR 464,126,813.93. This research is expected to be a reference for planning the implementation of similar building construction projects, especially in the context of using the PDM method.